Validation of the Turkish version of the Developmental Behavior Checklist: a comprehensive tool for assessing emotional, behavioral, and autism spectrum disorders in children and adolescents with intellectual disabilities - Sabide Duygu Uygun; Merve Çıkılı Uytun; Hande Konşuk Ünlü; Ayşegül Akgül Doğru; Serpil Aktaş Altunay; Didem Behice Öztop; Birim Günay Kılıç; Kerim Munir (Frontiers in Psychiatry)
IntroductionThe Developmental Behavior Checklist (DBC) is a standardized tool for evaluating emotional and behavioral concerns in children and adolescents with intellectual disabilities (ID) in clinical and research settings. This study aims to validate the Turkish versions of the DBC autism screening algorithm (ASA), parent (P) and teacher (T) forms.MethodsParents and teachers of 312 children and adolescents aged 4–17 with ID completed the Turkish versions of the DBC forms and the Strengths and Difficulties Questionnaire (SDQ). The presence of ASD or any other psychiatric disorder was assessed through clinical evaluation based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR) guidelines. Analyses of validity and reliability were conducted to evaluate the internal consistency, sensitivity, specificity, area under the curve (AUC), convergent validity, inter-rater reliability, and test-retest reliability.ResultsAmong the participants, 30.6% (n=70) had a psychiatric comorbid diagnosis according to the DSM-5-TR. DBC-P exhibited a sensitivity of 64.4%, a specificity of 87.6%, and an AUC of 76%. DBC-T demonstrated a sensitivity of 89.7%, a specificity of 75.8%, and an AUC of 82.7%. Additionally, 23.1% (n=45) were diagnosed with autism spectrum disorder (ASD). The DBC-ASA showed a sensitivity of 58.1%, a specificity of 64.6%, and an AUC of 61.3%. The DBC forms displayed strong internal consistency, robust test-retest reliability, and significant correlation with the SDQ measures. Inter-rater agreement between the DBC-P and DBC-T was low to moderate. A significant difference between parent and teacher assessments highlights the need for multi-informant approaches (p <.001).DiscussionThe DBC-P and DBC-T exhibit high validity and reliability, while the DBC-ASA shows moderate accuracy. This study acts as a valuable resource for clinicians, providing enhanced support for Turkish children and adolescents with ID.